A theory of pledge-and-review bargaining - Bård Harstad (University of Oslo, Department of Economics, 2022)
Inspired by the negotiations leading up to the Paris Agreement on climate change, I study a bargaining game where every party is proposing only its own contribution, before the set of pledges must be unanimously approved. I show that, with uncertain tolerance for delay, each equilibrium pledge maximizes an asymmetric Nash product. The weights on othersí payoffs increase in the uncertainty, but decrease in the correlation of the shocks. The weights vary pledge to pledge, and this implies that the outcome is generically inefficient. The Nash demand game and its mapping to the Nash bargaining solution follow as a limiting case. The model sheds light on the Paris climate change agreement, but it also applies to negotiations between policymakers or business partners that have differentiated responsibilities or expertise.
Keywords: C78; D78; 330; Bargaining games; the Nash program